The application of the associative mean spherical approximation in the theory of nonaqueous electrolyte solutions - Barthel, J.; Krienke, H.; Holovko, M.F.; Kapko, V.I.; Protsykevich, I.A. (Condensed Matter Physics, 2000)
Ionic association in electrolyte solutions is investigated in the framework of chemical models. The associative mean spherical approximation (AMSA) for electrolyte theory is reviewed. It is shown that AMSA in combination with the Ebeling association constant satisfactorily reproduces the thermodynamic measurement data up to high concentrations for nonaqueous solutions of solvents of relative permittivities in the range 20 < ε < 36 . For ionic solutions of lower permittivity the AMSA is modiﬁed by including ion trimers and tetramers to obtain a correct description of osmotic coefﬁcients and ionic conductivities.